Task board for the World Robot Summit 2020. (17th November 2022) - Shibata, Mizuho; Dobashi, Hiroki; Uemura, Wataru; Kotosaka, Shinya; Maeda, Yusuke; Aiyama, Yasumichi; Sakaguchi, Takeshi; Kawai, Yoshihiro; Noda, Akio; Yokoi, Kazuhito; Yokokohji, Yasuyoshi
Abstract : The World Robot Summit (WRS) Industrial Robotics Category tries to evaluate the performances of assembly robot systems using a task board. The task board comprises an assembly board (task board or board) and a set of parts assembled to the board. Utilizing an appropriate task board expects to facilitate the development of assembly robot systems. This paper examines the components necessary for the design of the task board through the results and analyzes of the task board competition in the WRS 2020 (held in September 2021). The task board will serve as a benchmark in developing an assembly robot system that can assemble the belt drive unit, an assembly model for the WRS 2020 assembly competitions. The success rate of each part of the competition and the correlation with assembly competitions reinforces the validity of the task board design. This paper describes that the WRS 2020 task board had a larger correlation with the belt drive unit used in the assembly competitions than that of the WRS 2018 (0.54 vs. 0.29). The design in the WRS 2020 is more appropriate than that in the WRS 2018 as a benchmark for assembling the belt drive unit. GRAPHICAL ABSTRACT: UF0001